2016
DOI: 10.1016/j.procs.2016.04.137
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity and Activeness of Crowd on Aged Pedestrian Dynamics

Abstract: An aging population is bringing new challenges to the management of escape routes and facility design in many countries. In this paper the movement properties of middle-and old-aged adults are studied with series of single-file movement experiments under laboratory conditions. The fundamental diagrams for two different groups of pedestrians and time-space diagrams are compared. For the groups with different composition and status, the fundamental diagrams are totally different but maintain the same trend. Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…For example, the elders are 40% slower than the adults when they walk in crowded urban walkways [20] and have lower speeds when they go downstairs [21]. The fundamental diagrams and step widths of pedestrians in single-file flow show great difference between elders and young adults [22][23][24]. The fundamental diagram of elderly pedestrians in straight corridors was studied in [25], where it was shown that differences in the dynamics can be observed, although by means of a transformation using the desired speed, the authors could show that the fundamental diagrams of elderly pedestrians can match the fundamental diagram of younger pedestrians.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the elders are 40% slower than the adults when they walk in crowded urban walkways [20] and have lower speeds when they go downstairs [21]. The fundamental diagrams and step widths of pedestrians in single-file flow show great difference between elders and young adults [22][23][24]. The fundamental diagram of elderly pedestrians in straight corridors was studied in [25], where it was shown that differences in the dynamics can be observed, although by means of a transformation using the desired speed, the authors could show that the fundamental diagrams of elderly pedestrians can match the fundamental diagram of younger pedestrians.…”
Section: Introductionmentioning
confidence: 99%
“…However, the large size of the cells and the discrete nature of the models dictate the use of the same size and speed for all of the pedestrians. In real world scenarios, pedestrians come in various sizes, and their movement speeds could significantly vary [39], [40]. The present study improves the accuracy of cellular automata models while keeping their advantages.…”
Section: Introductionmentioning
confidence: 86%
“…The speed range of 0-1.6 m/s is acceptable considering that the average speed of a pedestrian is around 1.3 m/s [44]. However, it is shown that pedestrian with different ages and health conditions have different walking speeds [39], [40]. These discrete choices (i.e., five possible values) limit the accuracy of the simulation and hinder the fine adjustments to the model with regard to pedestrian speed.…”
Section: Figure 1 Transition Of Pedestrians Into Neighboring Cells In...mentioning
confidence: 99%
“…In addition, the resulting density and movement speed are sensitive to the position of the measurement area and a valid time interval for the analysis. Nevertheless, the described methods are a proven approach for analysis and have been used in many prior studies, for instance in Germany, 4,53,54,57–71 Australia 72–77 Japan, 78–80 Palestine 81 and China 31–33,82,83 …”
Section: Methodsmentioning
confidence: 99%